Immunocytochemical correlation of peptides and tyrosine hydroxylase in nerve fibres of the human parotid gland - Heym, Christine; Webber, Richard; Adler, Detlev (Archives of oral biology, 1994)
The peptidergic innervation of parenchymal and vascular components in the human parotid gland was investigated by double-labelling fluorescence. Peptide immunoreactivity in nerve fibres was correlated with the presence of tyrosine hydroxylase (TH). By light microscopy, acinar innervation consisted of fibres with the combinations neuropeptide Y (NPY)/TH and NPY/vasoactive intestinal polypeptide (VIP). Some fibres were solely NPY, TH or VIP immunoreactive. Rarely, substance P (SP)/calcitonin gene-related (CGRP)-immunolabelled fibres were associated with acini. Intercalated ducts were often approached by NPY/TH- and VIP-containing fibres. VIP innervation of excretory ducts was sparse. Intralobular and intralobar excretory ducts, in addition to NPY and TH, revealed CGRP and CGRP/SP innervation, whereas nerve fibres on interlobar excretory ducts very rarely contained NPY and none of the other mediators. Vascular innervation consisted of NPY/TH and SP/CGRP fibres; in a few fibres SP was colocalized with leu-enkephalin. Large arteries were encircled by some VIP-positive fibres. The findings suggest a specific participation of neuropeptides and of peptide combinations in the regulation of parotid exocrine function.
Falsche Namensform: richtig Detlev Adler
Elektronische Reproduktion der Druck-Ausgabe 8. März 2004
Gesehen am 16.08.2023